Attitude control of aerial and underwater vehicles using single-input FUZZY P+ID controller. (February 2021) - Chen, Qi; Zhu, Daqi; Liu, Zhaobing
Abstract: This paper considers the attitude control problem of a new class of aerial and underwater vehicles with quadrotor structures. A novel single-input FUZZY P+ID attitude controller is proposed to improve the trans-media performance of the aerial and underwater vehicle. The proposed FUZZY P+ID controller has a unique feature to deal with the nonlinear uncertainties using a set of fuzzy rules from experts. Furthermore, the single-input structure of the fuzzy control allows for fast computation with the help of the signed distance method, which avoids using lengthy look-up tables. Numerical simulations show that the proposed single-input FUZZY P+ID controller offers superior performance to the conventional PID controller. The fully operational experiments demonstrated the robustness of the proposed controller for unmeasurable disturbances, such as the buoyancy and the drag force.